DELAYED DIAGNOSES OF PRADER WILLI SYNDROME IN A 19-YEAR-OLD - WA, Siti Sanaa; AR, Anilah; HR, Ijaz (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Prader-Willi syndrome (PWS) is a complex genetic disorder caused by lack of expression of genes on the paternally inherited chromosome 15q11.2-q13. Hypothalamic dysfunction has been implicated in many manifestations of this syndrome, including multiple endocrine abnormalities. These include growth hormone deficiency, central adrenal insufficiency, hypogonadism, hypothyroidism, and complications of obesity such as type 2 diabetes mellitus CASE We report a 19-year-old lady who was initially referred to the Endocrine Unit for primary amenorrhoea by a gynaecology clinic. She has one younger brother with normal pubertal development. Further history revealed that she had developmental delay and learning difficulty. She was also noted to have polyphagia and gradual weight gain since 3 years of age. Findings on physical examination were body mass index of 44 kg/m2 and height of 150 cm (below third centile), compared to midparental height of158 cm. Pubic hair and breast development were Tanner stage II. She had no features of Cushing's syndrome. Basal hormonal evaluation revealed follicle stimulating hormone (FSH) of 11 IU/L, luteinising hormone (LH) of 2.6 IU/L and low estrogen level of 19.4 pmol/L, indicative of secondary hypogonadism. Other hormone results were as follows: cortisol 158.6 nmol/L, insulin-like growth factor -1 (IGF-1) 99 µg/L (normal value 284 to 713), prolactin 10.34 ng/L, T4 14.6 pmol/L and TSH 1.40 mIU/L. Her 17-OH progesterone level was not elevated. Short Synacthen test showed adequate adrenal response. Magnetic resonance imaging of the brain reported a normal pituitary gland. Pelvic ultrasonography showed an anteverted uterus 5.6 cm x 2.5 cm with normal ovaries. Genetic study by DNA methylation testing confirmed the clinical diagnosis of PWS. She is currently managed by a multidisciplinary team consisting of a gynaecologist for cyclic oral contraceptive pills, occupational sports medicine for her weight loss program and dietary plans, and endocrinology for regular screening of endocrine manifestations of PWS. CONCLUSION PWS is a genetic syndrome in which early diagnosis and careful attention to detail regarding all the potential endocrine and behavioural manifestations can lead to a significant improvement in health and developmental outcomes. The importance of the roles of the providers caring for patients with PWS cannot be overstated.